Symmetries and Properties of the Energy-Casimir Mapping in the Ball-Plate Problem - Cristian Lăzureanu; Tudor Bînzar (Advances in Mathematical Physics)
In this paper a system derived by an optimal control problem for the ball-plate dynamics is considered. Symplectic and Lagrangian realizations are given and some symmetries are studied. The image of the energy-Casimir mapping is described and some connections with the dynamics of the considered system are presented.